2010
DOI: 10.1080/13548501003615258
|View full text |Cite
|
Sign up to set email alerts
|

Maternal postpartum depression and infant social withdrawal among human immunodeficiency virus (HIV) positive mother–infant dyads

Abstract: Maternal postpartum depression poses significant risks for mother-child interaction and long-term infant outcomes. Human immunodeficiency virus (HIV) status has also been implicated in the development of postpartum depression, but the association between maternal depression and infant social behavior in the context of HIV infection has not been fully investigated. First, we examined the relationship between maternal postpartum depression and infant social withdrawal at 10-12 months of age in HIV-infected mothe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
43
1
3

Year Published

2011
2011
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(50 citation statements)
references
References 29 publications
3
43
1
3
Order By: Relevance
“…Alcohol use in the current study was not associated with depressed mood in multivariate analysis, although it reached significance in the bivariate analysis. This concurs with the results of Hartley et al 5 Other factors that were significantly associated with a depressed mood in the current study in bivariate analysis included having an HIV-positive partner and inconsistent condom use with the primary partner. This seems to indicate that partner dynamics may influence the wellbeing of HIVinfected mothers.…”
Section: Discussionsupporting
confidence: 82%
See 4 more Smart Citations
“…Alcohol use in the current study was not associated with depressed mood in multivariate analysis, although it reached significance in the bivariate analysis. This concurs with the results of Hartley et al 5 Other factors that were significantly associated with a depressed mood in the current study in bivariate analysis included having an HIV-positive partner and inconsistent condom use with the primary partner. This seems to indicate that partner dynamics may influence the wellbeing of HIVinfected mothers.…”
Section: Discussionsupporting
confidence: 82%
“…Overall, 45.1% of women reported depressed mood in the postnatal period in the present study compared with 42.2% found in the study conducted by Hartley et al 5 in Cape Town and 54% meeting DSM-IV criteria for depression among urban primary clinic attendees in Zimbabwe. 28 The study found that the strongest predictors of depressed mood among postnatal women were having had an STI in the past 12 months, internalised stigma, discrimination experiences and lack of social support.…”
Section: Discussioncontrasting
confidence: 33%
See 3 more Smart Citations